Challenges in Mechanics of Time Dependent Materials, Volume 2 Proceedings of the 2017 Annual Conference on Experimental and Applied Mechanics - Arzoumanidis, Alex.; Silberstein, Meredith; Amirkhizi, Alireza; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
Challenges in Mechanics of Time-Dependent Materials, Volume 2 of the Proceedings of the 2017 SEM Annual Conference& Exposition on Experimental and Applied Mechanics, the second volume of nine from the Conference, brings together contributions to this important area of research and engineering.  The collection presents early findings and case studies on fundamental and applied aspects of Experimental Mechanics, including papers in the following general technical research areas:  Characterization Across Length Scales Extreme Environments & Environmental Effects Viscoelasticity Structure Function Performance Polymer Viscoplasticity Metallic Materials Fracture/Fatigue/Damage Composites Soft Materials.
Chap1. Experimental Characterisation of the Mechanical Properties of the Clay-Rock/Concrete Interfaces and Their Evolution in Time -- Chap2. Coupled Anisothermal Chemomechanical Degradation Solutions in One Dimension -- Chap3. Time-Temperature Analysis, DMA and Compression in PBXs -- Chap4. Statistical Life Time Prediction under Tension Loading for Unidirectional CFRP with Thermoplastics as Matrices -- Chap5. Time and Temperature Dependence on Tensile Strength of Unidirectional CFRP with Various Carbon Fibers -- Chap6. Time Temperature Superposition and Prony Series Coefficients of Asphalt Roof Shingle Material from Viscoelastic Creep Testing -- Chap7. A Mixture Theory with Interactive Body Forces for Composite Interphases -- Chap8. Material Creep Behavior with Prediction of Tertiary Creep Failure by a Spherical Micro-Indentation Method -- Chap9. Mechanical and Biodegradable Behavior of AZ31 Magnesium Alloy Immersed in Simulated Body Fluid -- Chap10. Failure of Laser Welded Structures Subjectedto Multiaxial Loading:  Experimental Development -- Chap11. Characterization and Modeling of PEEK in Histories with Reverse Loading -- Chap12. A Biomimetic Composite for Space Vehicle/Habitat Design -- Chap13. Interdependence of Size and Strain Rate in the Tensile Plastic Deformation of Single Crystal Silver Nanowires -- Chap14. Molecular Dynamics Motivated Maxwell Element Spring Nonlinearity -- Chap15. Keynote: Characterization and Simulation of Time-dependent Response of Structural Materials for Aero Structures and Turbine Engines (40-min).
Keywords: Mechanics, Applied; Solids; Materials -- Analysis; Building materials; Solid Mechanics; Characterization and Analytical Technique; Building Materials